(untitled) (Vanderbilt e-Journal of Luso-Hispanic Studies, 2016)
In this article, I trace the emergence and impact of legislation that regulated film in Argentina from 1957-1976—a tumultuous period given that military governments continually interrupted democratic administrations. Contrary to what has been long held that censorship began during the revolución libertadora, I make the case that censorship legislation was first passed during the democratic government of Arturo Frondizi (term of office 1958-1962). This legislation prioritized the projection of a poster-image of the nation, the protection of Catholic values, and the promotion of shared national beliefs. This early legislation paved the way for the instauration of film censorship in 1968—as well as the regulations on censorship approved up until March 1976, when a new dictatorship took over—, but was met with antagonism from several different social actors at that time. Several resonant cases illustrate the dynamic censorship-freedom of expression that characterized the 1958-1976 period.